2022
DOI: 10.3390/antiox11101940
|View full text |Cite
|
Sign up to set email alerts
|

Omarigliptin Mitigates 6-Hydroxydopamine- or Rotenone-Induced Oxidative Toxicity in PC12 Cells by Antioxidant, Anti-Inflammatory, and Anti-Apoptotic Actions

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are reported to exhibit promising effects on several pathological processes associated with Parkinson’s disease (PD). To explore its repositioning potential as an antiparkinsonian agent, we evaluated the effects of omarigliptin (OMG), a DPP-4 inhibitor recently approved as a hypoglycemic drug, on neurotoxin-induced toxicity, using PC12 cells as a cellular model of PD. The molecular mechanism(s) underlying its protective activity was also investigated. OMG alleviated ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the doses of ROT can increase several orders of magnitude, e.g., >330–1600 folds. For instance, the human dopaminergic SH-SH5Y neuroblastoma cells [ 63 ], the Lund human mesencephalic (LUHMES) cell line [ 64 ], iPSC-derived human dopamine neurons [ 65 ], as well as rat adrenal pheochromocytoma PC12 cells [ 66 ], and rat N27 dopaminergic cells [ 67 ] have been exposed to 10–50 μM ROT for different periods of time. In our experimental approach, we exposed the non-dopaminergic HEK-293 LRRK2 WT and KO cells to 50 μM for 6 h, which is a comparable condition to those reported in previously mentioned dopaminergic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the doses of ROT can increase several orders of magnitude, e.g., >330–1600 folds. For instance, the human dopaminergic SH-SH5Y neuroblastoma cells [ 63 ], the Lund human mesencephalic (LUHMES) cell line [ 64 ], iPSC-derived human dopamine neurons [ 65 ], as well as rat adrenal pheochromocytoma PC12 cells [ 66 ], and rat N27 dopaminergic cells [ 67 ] have been exposed to 10–50 μM ROT for different periods of time. In our experimental approach, we exposed the non-dopaminergic HEK-293 LRRK2 WT and KO cells to 50 μM for 6 h, which is a comparable condition to those reported in previously mentioned dopaminergic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that GSK-3β is accompanying to increase the oxidative stress, neuroinflammation, and dopaminergic neuronal apoptosis [73,99,100]. This can be justified by the capability of GSK-3β overexpression to negatively regulate Nrf2/HO-1 activation by promoting Nrf2 degradation while positively regulating NF-KB initiation by facilitating IKBα phosphorylation and NF-KB nuclear translocation [101,102]. Therefore, the observed GSK-3β overexpression might contribute to the ongoing oxidative stress, neuroinflammation, and neuronal apoptosis observed in the SI, MnCl 2 , or SI + MnCl 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrated that sitagliptin exerted substantial anti-inflammatory effects by modulating the levels of inflammatory factors like Nrf2 and NF-κb (Nader et al 2018). Omarigliptin exhibits anti-inflammatory effects by inhibiting NF-κB activation, leading to a reduction in nitric oxide (NO) production and the expression of inducible NO synthase (iNOS) in a model of neurotoxin-induced toxicity in PC12 cells, which mimics PD (Gouda and Cho 2022).…”
Section: Neuroprotective Effect Of Dpp-4 Inhibitorsmentioning
confidence: 99%